IMPROVING ENVIRONMENTAL SANITATION KNOWLEDGE OF SUGARCANE PROCESSING FARMERS GROUP IN NAGARI BATUBULEK, TANAH DATAR REGENCY - Ramli, Ramli; Desnita, Desnita; Darvina, Yenni; Mawardi, Mawardi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Nagari Batubulek is one of the sugarcane plantation areas in Tanah Datar regency, West Sumatra province, Indonesia. In nagari Batubulek itself, the “Marapalam Indah” farmer group processes sugar cane using a pressing machine and has 10 stoves to cook the cane into cane sugar. Every day this farmer group processes 750 kg of sugarcane into approximately 75 kg of cane sugar and 250 kg of bagasse. Currently, the bagasse produced is burned, as a result the smoke from the burning disturbs workers and pollutes the surrounding environment. Based on the results of interviews with the heads of farmer groups and several visits to the location of the kitchen for making sugar cane, it was found that the partner's problem was that farmers' knowledge in environmental sanitation were still low. The solution offered is to increase the knowledge and skills of partner communities to process bagasse into useful materials and to improve the sanitation of a clean kitchen environment through ongoing training and assistance. After the training and counseling, it was seen that the knowledge of environmental sanitation from the farmer groups had increased.